Analysis of m6A Methylation Modification Patterns and Tumor Immune Microenvironment in Breast Cancer - Dong, Menglu; Shen, Wenzhuang; Yang, Guang; Yang, Zhifang; Li, Xingrui (Frontiers in Cell and Developmental Biology, 2022)
In recent years, many studies have focused on the epigenetic regulation of immune response. The relationship between N6-methyladenosine (m6A) modification and specific tumor-infiltrating immune cells has also been confirmed in some literatures. However, the potential roles of m6A modification in tumor microenvironment (TME) remain unclear. Based on 23 kinds of m6A regulators, we comprehensively analyzed the m6A modification patterns in 983 samples, and correlated these modification patterns with TME immune cell infiltration. Principal component analysis (PCA) was used to construct the m6A scoring system to quantify the modification pattern of m6A in a single tumor patient. Three different m6A modification patterns were identified, and the invasion characteristics of TME cells were consistent with the three immune phenotypes including immune rejection, immune inflammation and immune desert. Our analysis showed that the prognosis of patients could be predicted by evaluating the m6A modification pattern in tumor. Low m6Ascore corresponded to increased mutation burden and immune activation, while stroma activation and lack of immune infiltration was observed in high m6Ascore subtypes. In addition, low m6Ascore was associated with enhanced response to anti-PD-1 / L1 immunotherapy. m6A modification pattern was closely related to breast cancer immune landscape. The comprehensive assessment of the m6A modification pattern in individual breast cancer patients will help to enhance our understanding of the invasive characteristics of TME and provides a new guidance for breast cancer patients with more effective immunotherapy strategies.